Emergent Management of Empyema - Ahmed, Osman; Zangan, Steven (Seminars in Interventional Radiology, 2012)
Empyema is a frankly purulent infection of the pleural space most often occurring secondary to parapneumonic effusion. Imaging, specifically contrast-enhanced computed tomography, plays a critical role in diagnosis with a “split pleura” sign being highly suggestive in the appropriate clinical setting. Diagnostic thoracentesis with culture and Gram stain further guides appropriate antibiotic therapy. Therapeutic drainage with small-bore tube thoracostomy has been shown to be a safe and effective treatment of early stage empyema. Augmentation of tube placement with intrapleural fibrinolytics and mucolytics facilitates catheter drainage by degrading loculations and decreasing fluid viscosity, respectively.
Keywords: empyema; chest tube; fibrinolytics; mucolytics; split pleura sign